EVALUATION OF THE FRESH PROPERTIES OF DOUM PALM FIBRE REINFORCED CONCRETE WITH RICE HUSK ASH AS PARTIAL REPLACEMENT OF CEMENT - Abdullahi, Musa; Abubakar, Idris; Kaura, Jibrin Mohammed; Lawan, Adamu; Garba, Isah (FUDMA Journal of Sciences, 2026)
Reinforced concrete flat slabs are widely adopted in modern buildings because of their structural efficiency and architectural flexibility; however, their performance is often governed by punching shear failure at slab–column connections. This study investigates the use of doum palm fibre (DF) as a natural fibre reinforcement and rice husk ash (RHA) as a partial replacement for cement, focusing on the fresh properties of fibre-reinforced concrete as a foundation for improving punching shear behaviour. Rice husk ash was used to replace Portland limestone cement at levels of 0, 5, 10, 15, 20, and 25%, while doum palm fibre was added at 0, 0.5, 1.0, 1.5, and 2.0% by volume of concrete. To improve fibre–matrix bonding, the fibres were chemically treated prior to mixing. The experimental programme was developed using Response Surface Methodology (RSM) implemented through Design-Expert software, allowing systematic evaluation of the combined effects of RHA and fibre dosage. Workability was assessed using slump flow and compacting factor tests in accordance with relevant British Standards.The results show that workability decreases gradually with increasing RHA content and fibre dosage due to higher water demand, fibre interlocking, and the fine, porous nature of RHA. Despite this reduction, all mixes remained within acceptable workability limits. Slump values ranged from 52.0 to 60.5 mm, while compacting factors varied between 0.90 and 0.92, indicating satisfactory compaction. An optimum mix containing 10% RHA and 1.0% DF was identified, offering a balanced combination of workability, fibre effectiveness, and pozzolanic performance.